2012
DOI: 10.1590/s0104-530x2012000200014
|View full text |Cite
|
Sign up to set email alerts
|

A transferência de tecnologia universidade-empresa no contexto brasileiro: uma revisão de estudos científicos publicados entre os anos 2005 e 2009

Abstract: O tema da gestão da inovação e transferência de tecnologia (TT) no contexto de interação universidade-empresa é relativamente novo no Brasil e emergente em âmbito internacional (REISMAN, 2005), assim, seus dados e teorias ainda se apresentam de modo fragmentado. Considerando essa fragilidade, este estudo objetivou identificar e analisar pesquisas recentes publicadas no Brasil sobre o tema, buscando contribuir para a consolidação desse corpo teórico. O trabalho, de cunho exploratório, revisou as pesquisas publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
30

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 16 publications
0
22
0
30
Order By: Relevance
“…The collaboration between universities and companies as a means to boost OI is the object of research of most of the studies identified (Alves & Pimenta-Bueno, 2014;Castro et al, 2014;Carrijo & Botelho, 2013;Closs & Ferreira, 2012;Fernandes et al, 2016;Gielfi et al, 2017;Matei et al, 2015;Oliveira & Balestrin, 2015;Schaeffer et al, 2015;Silva et al, 2013b;Stal & Fujino, 2016). Closs & Ferreira (2012) point out that university-company collaboration tends to be positive for companies because, in addition to reducing innovation costs, it also allows greater access to qualified people and university structures, especially laboratories. The findings of Castro et al (2014) suggest that the company-university relationship in Brazil tends to improve the innovative performance of firms.…”
Section: Presentation Of Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The collaboration between universities and companies as a means to boost OI is the object of research of most of the studies identified (Alves & Pimenta-Bueno, 2014;Castro et al, 2014;Carrijo & Botelho, 2013;Closs & Ferreira, 2012;Fernandes et al, 2016;Gielfi et al, 2017;Matei et al, 2015;Oliveira & Balestrin, 2015;Schaeffer et al, 2015;Silva et al, 2013b;Stal & Fujino, 2016). Closs & Ferreira (2012) point out that university-company collaboration tends to be positive for companies because, in addition to reducing innovation costs, it also allows greater access to qualified people and university structures, especially laboratories. The findings of Castro et al (2014) suggest that the company-university relationship in Brazil tends to improve the innovative performance of firms.…”
Section: Presentation Of Results and Discussionmentioning
confidence: 99%
“…Although many studies on OI address efforts to analyze the university-company relationship, some of these indicate that there are difficulties inherent in carrying out this kind of collaboration in Brazil (Closs & Ferreira, 2012;Alves & Pimenta-Bueno, 2014;Fernandes et al, 2016). For example, Fernandes et al (2016) observed that universities-notably engineering schools-contribute more to workforce formation than to economic collaborations with industries.…”
Section: Presentation Of Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Innovation is taken into consideration by many as one of the major factors for the organizational and human development, becoming the main creator of competitive advantage, searching for more and more distinction among competitive companies, as the main key for the sustainability of the highly aggressive market (RABECHINI JÚNIOR; CARVALHO; LAURINDO, 2002;CLOSS;FERREIRA, 2012).…”
Section: Innovation Process Characteristicsmentioning
confidence: 99%
“…Uma das formas de incentivar a geração de inovações tem ocorrido por meio da compreensão do processo de transferência de tecnologia, caracterizado pela passagem de conhecimentos gerados pela universidade a uma empresa que lhe permite inovar e ampliar sua capacidade tecnológica, possibilitando-lhe obter uma vantagem competitiva no mercado (Closs & Ferreira, 2012).…”
Section: Introductionunclassified